Pelatihan Pengolahan Bahan Pangan Dan Digitalisasi Produk Potensi Desa Ngulan Kulon Pogalan Trenggalek - Siswahyudianto, Siswahyudianto; Yudhataruna, Dhimas (Cahaya Pengabdian, 2025)
This community service activity was conducted in Ngulankulon Village, Trenggalek, with the aim of increasing the capacity of Micro, Small, and Medium Enterprises (MSMEs) through training in food processing and product digitalization. The main challenges faced by the village community are limited knowledge in optimally processing agricultural products and the minimal use of digital technology for product marketing. The training activity was designed with two main focuses: an introduction to technology-based food processing techniques such as fermentation, drying, and packaging, and training in the use of social media and e-commerce platforms to market products widely. The training method was carried out in a participatory, community-based manner and was followed by post-training mentoring to ensure sustainable implementation. Evaluation results showed that participants experienced significant improvements in technical food processing skills and digital literacy. Several MSMEs succeeded in extending product shelf life, improving product quality, and expanding markets through online marketing. The local economic impact began to be seen in increased sales volume and consumer reach beyond the region. This activity also encouraged the growth of innovation and creativity in product development based on local potential, and strengthened awareness of the importance of digitalization for business sustainability. Overall, this program contributed positively to empowering the village economy through an applied technological approach and training